Handling Anarchist Demonstrations That Are Harmful to the Community Based on Police Standard Operating Procedures in the Jurisdiction of Polda Metro Jaya - Sihombing, Jasalmon; Markoni; Kantikha, I Made; Nardiman (GoAcademica Research & Publishing, 2025)
Demonstrations, as a form of freedom of expression, often present challenges for security forces, especially when such actions escalate into anarchic behavior that harms the public. In the legal jurisdiction of the Metro Jaya Police, this issue has become a significant concern due to the high frequency of demonstrations in the capital city. This study aims to analyze the Police's Standard Operating Procedures (SOP) in dealing with anarchic demonstrators within the jurisdiction of the Metro Jaya Police. The theories used in this research are law enforcement theory and legal protection theory, employing a normative juridical research method. The results of the study show that the implementation of the Police SOP, which includes stages of prevention, crowd control, and evaluation, plays a significant role in addressing anarchic actions. Challenges such as limited coordination with the organizers, limited resources, and difficulties in maintaining transparency and accountability were identified. In conclusion, the Police SOP at the Metro Jaya Police is designed to handle anarchic demonstrations in a structured, professional, and legal manner, with stages from prevention to the use of measured force, prioritizing transparency, accountability, and the protection of human rights.